Grain size effect on yield strength of titanium alloy implanted with aluminum ions - Popova N. A. Nataljya Anatoljevna; Nikonenko E. L. Elena Leonidovna; Yurjev I. Yu. Ivan Yurjevich; Kalashnikov M. P. Mark Petrovich; Kurzina I. A. Irina Aleksandrovna (2016, 2016)
Title screen